Analysis of Deviant Behavior that Occurs at SMA 1 Bukit Sundi - Lisa Rahmawati; Afrahamiryano (Penerbit Hellow Pustaka, 2024)
Deviant behavior carried out by teenagers generally occurs when they are in middle school (SMP) and high school (SMA). This is because during this period, adolescents are in a phase that is vulnerable to external influences, and the adolescent's psyche is still in an unstable state. At this school age, teenagers can receive various influences, both positive and negative, which can influence their behavior. The aim of this research is to determine the influence of deviant behavior in high school children in the learning process at school. Deviant behavior is behavior that is not in accordance with the stages of improvement and is not always in accordance with relevant norms. Deviant behavior here is also called negative behavior. The results of the research show that forms of deviant behavior among students who enter counseling at SMA 1 Bukit Sundi include frequently missing school, not being polite in talking to teachers, and also not participating in lessons at school, fighting with their friends. There are quite a lot and varied behavioral deviations that have been carried out by students, therefore students must be given sufficient provisions so that they do not fall into the wrong company.